2021
DOI: 10.3340/jkns.2020.0071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mutant Isocitrate Dehydrogenase 1 Immunoexpression, Ki-67 and Programmed Death Ligand 1 in Diffuse Astrocytic Tumours : Study of Single Center in Bandung, Indonesia

Abstract: Objective : Diffuse astrocytic tumour (DAT) is a diffuse infiltrative astrocytoma tumour accompanied by molecular parameters such as the presence or absence of isocitrate dehydrogenase (IDH) gene mutations. Ki-67 is a marker for DAT proliferation, while programmed death ligand 1 (PD-L1) indicates an immune evasion mechanism. This study aimed to analyze the correlation among mutant IDH1 R132H, Ki-67, and PD-L1 immunoexpression in the DAT. Methods : A cross-sectional study was carried out on 30 paraffin blocks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In this study, our findings showed that PD-L1 was identified in 81.73% of astrocytoma cases, while IDH1 was detected in 73.3%. Similarly, both Xue et al, (2017) and Bolly et al, (2021) reported expression rate of PD-L1 (78% and 70%, respectively), which was close to our results. As well, Nazari et al, (2020), andBolly et al, (2021), reported higher PD-L1 expression among the high-grade group (100% and 87.5%, respectively).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, our findings showed that PD-L1 was identified in 81.73% of astrocytoma cases, while IDH1 was detected in 73.3%. Similarly, both Xue et al, (2017) and Bolly et al, (2021) reported expression rate of PD-L1 (78% and 70%, respectively), which was close to our results. As well, Nazari et al, (2020), andBolly et al, (2021), reported higher PD-L1 expression among the high-grade group (100% and 87.5%, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, both Xue et al, (2017) and Bolly et al, (2021) reported expression rate of PD-L1 (78% and 70%, respectively), which was close to our results. As well, Nazari et al, (2020), andBolly et al, (2021), reported higher PD-L1 expression among the high-grade group (100% and 87.5%, respectively). A lower rate of IDH1 mutation was reported by Nazari et al (2020) (20%) and July et al, (2020) (17%), which could be attributed to the larger sample size.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The annual incidence of malignant gliomas is about 5 cases per 100,000 person-years [ 1 ]. Astrocytic tumors (pilocytic astrocytoma, diffuse astrocytoma, anaplastic astrocytoma, glioblastoma, or all other gliomas) account for 76.4% of all gliomas [ 2 ].…”
Section: Introductionmentioning
confidence: 99%